EQUITY AND EQUALITY IN CUSTOMARY MODES OF INHERITANCE AMONG THE YORUBA OF SOUTHWESTERN NIGERIA (2015)
There was concentration dependent, significant induction of micronucleus in the erythrocytes of C. gariepinus (OSL = 1.4±0.0 – 9.6±0.2; AEL = 0.8±0.4 – 8.6±0.6), bone marrow cells of C. japonica (OSL = 1.0±0.2 – 2.1±0.6; AEL = 0.7±0.1 – 3.2±0.6) and M. musculus (OSL = 5.5±0.6 – 18.5±0.0; AEL = 6.5±0.3 – 18.1±1.3). There was significant increase in ALT (OSL= 31.1±2.1 – 52.7±1.6 IU/L; AEL = 30.7±1.5 – 49.5±1.3 IU/L) and AST (OSL = 86.9±13.2 – 168.4±1.0 IU/L; AEL = 84.5±1.5 – 161.9±1.2 IU/L), but significant decrease in albumin level (OSL = 2.6±0.2 – 5.11±0.3 g/dL; AEL = 2.7±0.2 – 5.2±1.2 g/dL) in serum of exposed rats compared to the negative control. Necrosis and vacuolation of the hepatocytes; cortical congestion and haemorrhage in the kidney; and infiltration of macrophages, inflammation and apoptotic lymphocytes in the thymus were observed in exposed rats. The frequencies of these anomalies were higher in OSL than AEL exposed animals. The concentrations (mg/L) of BOD (306.0 – 601.0), copper (0.9 – 3.9), manganese (0.6 – 3.9), lead (0.8 – 2.1), chromium (1.4 – 2.4) and cadmium (0.3 – 2.2) were above NESREA wastewater limits. The frequency of complaints of bad odour (OSL, 95.4%; AEL, 90.1%) and dermal contacts with vermin (OSL, 80.8%; AEL, 54.2%); respiratory (OR=9.7, 95% CI=6.6 – 14.6), dermal (OR=7.2, 95% CI=4.8 – 10.8) and gastrointestinal (OR=7.9, 95% CI=6.2 – 12.1) anomalies were significantly higher among residents nearer (2 km) the landfills.